Narratives of Secular Nationalism in Salman Rushdie’s “Midnight’s Children” and “The Moor’s Last Sigh” (Glocalism: Journal of Culture, Politics and Innovation, 2019)
Nationalism as a theoretical category is a widely disputed and elusive concept. This is due to the fact that the formulation of the nation-space across widely scattered geographies has now to take into account an altered dynamics of interaction and exchange. The relevance of literary language as an aesthetic register to corroborate the nation as “a powerful historical idea” and the need to formulate suitable analogies reveal the inadequacy of mapping the project through territorial credentials alone. The socio-cultural currency of the idea of the nation as a geographical continuum inserts itself into the pedagogical language of narration. The nation as an entity is not coterminous with its political cartography, in spite of the persistent efforts of all nationalist discourses to contain the narrative of the nation within an identifiable trajectory. To make a detour, to bypass and circumvent certain institutional codifications and create an audible register of displaced voices, is to interrupt the process of seamless narration and alter its constitutional chemistry. The nation as a barbed wire territory secured from the human contamination of the “other” – through paperwork, legal permits and manning of entry points – already hints at its fragile contours. The incongruent coupling of culture and polity, the increased involvement of armed forces along various corridors of cultural transaction, the enactment of geopolitics on a global scale, the susceptibility of culture to the tropes of power – all call into question the authenticity of the rhetoric of nationalism and its efficacy in healing differences and mending fractures. There is an increasing need to re-conceptualize the nation as a tentative space marked by an internal mobility of its constituents, where it is possible to articulate differences while dispensing with the abrasive rhetoric of fundamentalism. The nation thus becomes a fluid space of confluence and convergence, “a gestative political structure” gesturing towards a more inclusive space – perhaps exploring the possibilities that globalization has to offer in terms of pluralist cultural connotations.
Keywords: nation; culture; polity; fundamentalism; globalization